Pengaruh Budaya Orgnisasi Dan Pelatihan Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening (PT. Baja Karya Utama Bekasi) - Tio Fahri Dianmas; Novi Fitria Hermiati (Universitas Hamzanwadi, 2023)
Company employees become an asset when job satisfaction alongside performance is considered. The purpose of this study is to find out how job satisfaction and the relationship between training and organizational culture affect employee performance. This research is quantitative and collects data through a questionnaire. This study has a population of 100 people and a sample of 80 employees. combines random sampling with probability sampling techniques. The number of samples to be used in the study was determined using the Slovin formula. Structural Equation Modeling (SEM) with Lisrel software will be used for hypothesis testing analysis techniques. then the results are obtained where Organizational Culture influences Employee Performance, Training influences Employee Performance, Organizational Culture does not affect Job Satisfaction, Training influences Job Satisfaction, Job Satisfaction affects Employee Performance, Organizational Culture does not affect Employee Performance which is mediated by Satisfaction Work, Training has an effect on Employee Performance which is mediated by Job Satisfaction